Screening for elevated blood lead levels using single hair strands: Accounting for external contamination - Jennie R. Christensen; Geriene O. LaBine; Joyce McBeth (Elsevier, 2023)
Hair has long been explored as a potential biomarker of lead exposure since lead is readily adsorbed into hair's keratinous matrix; however, the utility of hair as a biomarker for lead exposure is hampered by its susceptibility to external contamination: lead particles attach to the exposed hair surface, confounding estimates of endogenous concentrations. This study describes the development of a hair screening tool, in which the confounding influence of external contamination are mitigated by focusing on the unexposed hair root, to predict elevated blood lead levels (BLLs). This tool requires a single strand of scalp hair, which is analyzed using laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Forty-four (44) workers with high potential for lead exposure, and 63 reference individuals (with no known lead exposure) volunteered for the study. Hair lead level (HLL) thresholds were developed using methods from clinical assessment to screen exceedances of BLL thresholds at 10 and 15 µg/dL. Hair from both groups showed significantly lower lead concentrations in below-scalp portions compared to above the scalp (above-scalp was 11.2 times higher in workers, and 3.7 times higher in reference group). Hair lead concentrations below the scalp in workers significantly predicted BLLs. HLL thresholds for screening BLLs were 0.60 mg/kg and 0.75 mg/kg for BLLs of 10 µg/dL and 15 µg/dL, respectively. These HLL thresholds yielded high sensitivity (>85%), and slightly lower specificity (67% and 33%, for BLL thresholds of 10 µg/dL and 15 µg/dL, respectively). This study provides reference HLLs in non-contaminated portions of hair (<0.097 mg/kg), shows the significance of external contamination on exposed portions of hair even in a reference population, and assesses the effectiveness of below-scalp hair as a biomarker of elevated lead exposure. This hair screening tool effectively predicted BLL exceedances and could be considered as a non-invasive alternative to blood sampling.